Total synthesis of decarboxyaltenusin - Warmuth, Lucas; Weiß, Aaron; Reinhardt, Marco; Meschkov, Anna; Schepers, Ute; Podlech, Joachim (Beilstein Journal of Organic Chemistry, 2021)
The total synthesis of decarboxyaltenusin (5’-methoxy-6-methyl-[1,1’-biphenyl]-3,3’,4-triol), a toxin produced by various mold fungi, has been achieved in seven steps in a yield of 31% starting from 4-methylcatechol and 1-bromo-3,5-dimethoxybenzene, where the longest linear sequence consists of five steps. The key reaction was a palladium-catalyzed Suzuki coupling of an aromatic boronate with a brominated resorcin derivative.
Keywords: biaryls; boronates; mycotoxins; polyketides; Suzuki coupling